Investigation of the gastric digestion behavior of commercial infant formulae using an in vitro dynamic infant digestion model - Descallar, Faith Bernadette; Roy, Debashree; Wang, Xin; Zhu, Peter; Ye, Aiqian; Liang, Yichao; Pundir, Shikha; Singh, Harjinder; Acevedo-Fani, Alejandra (Frontiers in Nutrition, 2024)
The gastric digestion behavior of different commercial Stage 1 infant formulae (for 0-6 months) with different formulation backgrounds was investigated using an in vitro dynamic infant human gastric simulator (iHGS). The microstructural arrangements of the protein and lipid, colloidal stability and protein hydrolysis during digestion were elucidated. During gastric digestion, casein-dominant formulations showed a higher extent of aggregation due to their high proportion of casein micelles that underwent coagulation upon acidification and via the action of pepsin. The extensive protein coagulation/curd formation in casein-dominant infant formulae slowed the rate of protein hydrolysis and resulted in the retention of caseins in the iHGS for longer times. Confocal micrographs showed that oil droplets were entrapped in the curd particles of casein-dominant infant formulae, which consequently slowed the gastric emptying of lipids. Conversely, whey-dominant formulations showed a lower degree of protein aggregation that resulted in faster protein hydrolysis and rapid protein and lipid emptying from the iHGS. It was also revealed that whey-dominant infant formulae in the presence of biopolymers increased the viscosity of gastric chyme and induced the flocculation of oil droplets. This altered the rate of protein hydrolysis and emptying of lipids. Correlation analyses depicted the overall kinetics of gastric emptying of macronutrients during digestion and comprised two stages: (i) driven by the continuous stomach emptying and (ii) influenced by aggregation and coalescence indices. The present study highlights the similarities and differences in the digestion behaviors of commercial infant formulae based on important ingredients such as types of proteins and biopolymers, regardless of the formulation or processing histories.